Ki Hajar Dewantara's Philosophy of Education in the Perspective of Oumar Muhammad Al-Toumy Al-Syaibani and Its Implications of Islamic Education - Ahmad, Agus; Setiawan, Dedi; Mushodiq, Agus (International Journal on Advanced Science, Education, and Religion, 2025)
This research aims to analyze Ki Hajar Dewantara's educational philosophy as contained in the Philosophers of Education trilogy "The Ngarsa Sung Tulada, The Madya Mangun Karsa, Tut Wuri Handayani" from the perspective of Oumar Muhammad Al-Toumy Al-Syaibani, a figure in contemporary Islamic education. This approach aims to explore the meeting point between the noble values of national education and the principles of Islamic education based on monotheism. By using qualitative-descriptive methods and literature study, this research concludes that there is philosophical harmony between Ki Hajar's humanistic approach and Al-Syaibani's spiritual education. The integration of the two is an important foundation in developing the Islamic Religious Education (PAI) curriculum in Indonesia to make it more contextual, spiritual and liberating. This article recommends the active role of teachers as moral and spiritual role models in designing education that is independent and has transcendental value.